PERBANDINGAN PENGAJARAN DENGAN MENGGUNAKAN KBK (KURIKULUM BERBASIS KOMPETENSI) DAN KTSP (KURIKULUM TINGKAT SATUAN PENDIDIKAN) - Endang Widuri (Universitas Negeri Medan, 2012)
abstract Curriculum as a design in education has a strategic position, as all educational activities geared to the curriculum. Basically the curriculum is a system consisting of several components. Curriculum components of an educational institution can be identified by reviewing books education curriculum. In the classical view, the curriculum is seen as a lesson plan in a school or lessons and materials that must be taken at school. Meanwhile, according to the modern view, the curriculum as a lesson plan, regarded as something real happening in the education process in schools. Kata kunci : pengertian kurikulum, fungsi dan tujuan kurikulum, pengertian KBK, tujuan, landasan dan ciri-ciri KBK, pengertian KTSP, tujuan, landasan dan ciri-ciri KTSP, perbedaan KBK dan KTSP.